2016
DOI: 10.1021/acs.jafc.6b02196
|View full text |Cite
|
Sign up to set email alerts
|

Stable Isotope Resolved Metabolomics Reveals the Role of Anabolic and Catabolic Processes in Glyphosate-Induced Amino Acid Accumulation in Amaranthus palmeri Biotypes

Abstract: Biotic and abiotic stressors often result in the buildup of amino acid pools in plants, which serve as potential stress mitigators. However, the role of anabolic (de novo amino acid synthesis) versus catabolic (proteolytic) processes in contributing to free amino acid pools is less understood. Using stable isotope-resolved metabolomics (SIRM), we measured the de novo amino acid synthesis in glyphosate susceptible (S-) and resistant (R-) Amaranthus palmeri biotypes. In the S-biotype, glyphosate treatment at 0.4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
42
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 41 publications
7
42
0
Order By: Relevance
“…And, the significant depletion in tryptophan level was clustered with depletion of valine and thymidine (Figure 3). In accordance with our results, impairment of pathways involved in energy metabolism (Orcaray et al, 2012) and protein synthesis (Maroli et al, 2016) were found in glyphosate-treated plants. Intracellular accumulation of AAs and depletion in protein synthesis have been reported for the glyphosate-sensitive biotype of the flowering plant Amaranthus palmeri (Maroli et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…And, the significant depletion in tryptophan level was clustered with depletion of valine and thymidine (Figure 3). In accordance with our results, impairment of pathways involved in energy metabolism (Orcaray et al, 2012) and protein synthesis (Maroli et al, 2016) were found in glyphosate-treated plants. Intracellular accumulation of AAs and depletion in protein synthesis have been reported for the glyphosate-sensitive biotype of the flowering plant Amaranthus palmeri (Maroli et al, 2016).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with our results, impairment of pathways involved in energy metabolism (Orcaray et al, 2012) and protein synthesis (Maroli et al, 2016) were found in glyphosate-treated plants. Intracellular accumulation of AAs and depletion in protein synthesis have been reported for the glyphosate-sensitive biotype of the flowering plant Amaranthus palmeri (Maroli et al, 2016). This was proposed to be due to the metabolic response of the plant to the abiotic stressor (Maroli et al, 2016), which may include a decrease in de novo protein synthesis.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The effect of the herbicide is not restricted to the inhibition of aromatic amino acid biosynthesis alone. It also disrupts the de novo biosynthesis of most non-aromatic amino acids, coupled with decreased protein synthesis (Maroli et al, 2016). In consequence, growth is inhibited (Pline et al, 2002;Orcaray et al, 2012), the transport of assimilates is reduced (Yanniccari et al, 2012a) and photosynthetic CO 2 assimilation decreases significantly (Olesen and Cedergreen, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In consequence, growth is inhibited (Pline et al, 2002;Orcaray et al, 2012), the transport of assimilates is reduced (Yanniccari et al, 2012a) and photosynthetic CO 2 assimilation decreases significantly (Olesen and Cedergreen, 2010). Several of these effects are limited or absent in glyphosate-resistant weed plants treated with the herbicide (Yanniccari et al, 2012a,b,c;Maroli et al, 2016).…”
Section: Introductionmentioning
confidence: 99%